Thermal conductivity of rice straw polypropylene particleboard. Issue 1 (February 2021) - Ismail, I; Fitri, N; Mursal,; Fadzullah, S H S
Abstract: The availability of rice straw in Indonesia, including in some other Asian countries, is very abundant. However, it has not been used optimally. One possibility of using rice straw is for heat insulation in buildings. This study aims to analyze the thermal conductivity of rice straw polypropylene composite/particleboard. In this study, particulate composites from rice straw have been produced by using recycled plastic polypropylene (homopolymer) as adhesive. The particle size of rice straw used in this study was 20 mesh. The composition of rice straw and polypropylene were varied (the ratio of rice straw particle to polypropylene is 30/70 wt. %, 40/60 wt. %, 50/50 wt. %, and 60/40 wt. %). The composite samples were produced by using a hot press with 3 tons of load. The thermal conductivity of rice straw composite samples has been measured. We found that our composite thermal conductivity is 0.223 (±0.015) W/m °C for rice straw 30 wt.% and polypropylene 70 wt. %. For rice straw composition 60 wt. %, its thermal conductivity reduces to 0.191 (±0.002) W/m °C. The composite thickness swelling is found to be 0.76 (±0.26) % for rice straw 30 wt.% (after 24 hours immersing in water). The percentage of thickness swelling is 1.80 (±0.10) % for rice straw 60 wt. %. The results of our study revealed that the thermal conductivity of rice straw composite decreased as the thickness swelling increased. This behavior is related to the porosity of the composite.